A plant-inspired long-lasting adhesive bilayer nanocomposite hydrogel based on redox-active Ag/Tannic acid-Cellulose nanofibers. (1st March 2021) - Chen, Yajun; Zhang, Yanan; Mensaha, Alfred; Li, Dawei; Wang, Qingqing; Wei, Qufu
Highlights: Ag/TA-CNF triggered the dynamic quinone/catechol reaction inner the hydrogel. The hydrogel exhibited repeatable and long-lasting tissue adhesiveness. NIR-enhanced and Ag-endowed synergistic antibacterial capacity. The bilayer structure enhanced the mechanical properties. Abstract: Long-lasting and reusable adhesive hydrogels are highly desirable in biomedical and relevant applications, however, its design still remains challenge. Here, a series of plant-inspired adhesive hydrogels were prepared based on Ag/Tannic acid-Cellulose nanofibers (Ag/TA-CNF) triggered reversible quinone/catechol chemistry, which mimicked the long-lasting reductive/oxidative balance in mussels. The dynamic redox system generated catechol groups inner the hydrogel continuously, imparting hydrogels with high and repeatable adhesiveness. Besides, the hydrogel still maintained its high adhesiveness after storing at extreme temperatures for 30 days. Furthermore, to broaden the biomedical applications of the hydrogels, the pre-gel solution with optimal composition was cast onto the surface of vaccarin-loaded electrospun nanofibers to form the bilayer nanocomposite hydrogel (NF@HG) in situ . The NF@HG with the intrinsic properties of the hydrogel layer (e.g. stretchable, adhesive, antioxidant, antifreezing, antidrying, photothermal and antibacterial) exhibited enhanced mechanical properties, sustained drug release and good cytocompatibility, which could be an attractive candidate for wound healing material. Taken together, this study may inspire new aspects for designing reusable and long-lasting adhesive hydrogels according to dynamic catechol chemistry.